2016
DOI: 10.1017/thg.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Manifestations of Twin–to–Twin Transfusion Syndrome

Abstract: This review addresses the physiology of monochorionic diamniotic (MC/DA) twins and the potential for twin-twin transfusion syndrome (TTTS). It focuses on the underlying cardiovascular pathophysiology of TTTS and the cardiovascular impact of TTTS for both the recipient and the donor twin. It explains the principles for assessment and monitoring of these cardiovascular changes and how these may be used to guide pregnancy management. Finally, it describes the effect of treatment on the altered hemodynamics and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 66 publications
1
24
1
Order By: Relevance
“…Because most studies on this topic focus on recipients with preintervention RVOTO and lack longitudinal prospective follow‐up on all recipients, detection of these late‐onset cases is rarely described before . Initial mild RVOTO after birth is however important, as it may progress to severe RVOTO with need for intervention in infancy . The total incidence of postnatal RVOTO found in this study is slightly higher than in prior large cohort studies, which found an incidence of 2.1% to 4% .…”
Section: Commentscontrasting
confidence: 55%
See 1 more Smart Citation
“…Because most studies on this topic focus on recipients with preintervention RVOTO and lack longitudinal prospective follow‐up on all recipients, detection of these late‐onset cases is rarely described before . Initial mild RVOTO after birth is however important, as it may progress to severe RVOTO with need for intervention in infancy . The total incidence of postnatal RVOTO found in this study is slightly higher than in prior large cohort studies, which found an incidence of 2.1% to 4% .…”
Section: Commentscontrasting
confidence: 55%
“…Several pathways of RVOTO development have been suggested, such as the underdevelopment of the pulmonary valve due to decreased forward flow across the PV, caused by right ventricular hypertrophy, the effect of endothelial damage caused by shear stress, which eventually results in valve dysplasia and damage of the valve due to exposure to abnormal concentrations of vasoactive mediators such as endothelin‐1, renin, and angiotensin II . The decreased flow across the PV may be explained by impaired cardiac function at the time of TTTS .…”
Section: Commentsmentioning
confidence: 99%
“…Recent reports have indicated that the aforementioned cardiovascular disorders can remain even after FLP treatment, and there are frequently observed right side cardiac anomalies in the recipient, appeared as pulmonary artery stenosis and functional atresia 7,32,33 . The authors have also experienced cases where functional pulmonary valve atresia developed after birth, similar to reports that described a right-side circular shunt where the ductus arteriosus flow also had a left-to-right shunt due to the presence of pulmonary artery regurgitation and tricuspid regurgitation from the fetal stage 34,35 . As described, cardiovascular complications can remain even after curative therapy for TTTS.…”
Section: Cardiovascular Complications Of Fetoscopic Lasersupporting
confidence: 70%
“…Although fetal functional and/or structural cardiac abnormalities improve after successful laser surgery, they can persist beyond birth and sometimes require intervention. Cardiovascular complications are primarily seen in the recipient twin and include hypertension, cardiomyopathy, right ventricular outflow tract obstruction (which affects about 4% of recipients at birth) and persistent pulmonary hypertension of the newborn [56,57]. However, donors may be at increased risk for aortic coarctation, possibly due to reduced flow caused by hypovolemia [58].…”
Section: Neonatal Outcomementioning
confidence: 99%